(untitled) (Communications in Computational Physics, 2008)
We study the biofilm-flow interaction resulting in biofilm growth, deformation and detachment phenomena in a cavity and shear flow using the phase field model developed recently [28]. The growth of the biofilm and the biofilm-flow interaction in various flow and geometries are simulated using an extended Newtonian constitutive model for the biofilm mixture in 2-D. The model predicts growth patterns consistent with experimental findings with randomly distributed initial biofilm colonies. Shear induced deformation, and detachment in biofilms is simulated in a shear cell. Rippling, streaming, and ultimate detachment phenomena in biofilms are demonstrated in the simulations, respectively, in a shear cell. Possible merging of detached biofilm blobs in oscillatory shear is observed in simulations as well. Detachment due to the density variation is also investigated shedding light on the possible bacteria induced detachment.